Effects of Na2CO3/Na2SO4 on catalytic gasification reactivity and mineral structure of coal gangue. (15th September 2022) - Miao, Hengyang; Wang, Zhiqing; Wang, Zhefan; Sun, Haochen; Li, Xiangyu; Liu, Zheyu; Dong, Libo; Zhao, Jiantao; Huang, Jiejie; Fang, Yitian
Abstract: In this work, CO2 catalytic gasification was applied to the utilization of coal gangue (CG). The differences between Na2 CO3 and Na2 SO4 catalysts on the effects of the catalytic and activation reaction were evaluated comprehensively. Gasification reactivity and aluminum extraction yield were improved in the presence of both alkali metal salts and increased with increasing temperature at 800–1000 °C. The minerals species in Na2 SO4 loaded ash (SCA) varied a lot from 800 °C to 850 °C, and the extraction yield can reach the peak (91.39%) at 850 °C. The aluminum ions solution obtained from SCA was purer than that from Na2 CO3 loaded ash (CCA), this was owing to that SCA has more compact Si–O bond than CCA. What's more, according to the DFT results, Na2 SO4 had a stronger ability to lengthen the Al–O bond and activate the aluminum in minerals. Besides these, it was found that the sodium in SCA was more favorable for accelerating gasification in theory. This research will contribute to the realization of high-value utilization of CG and Na2 SO4 . Graphical abstract: Image 1 Highlights: The concept of using Na2 SO4 to activate coal gangue is put forward innovatively. Na2 SO4 has a good effect on gasification process and activation of minerals at 850–900 °C. The activation mechanism of minerals in coal gangue was discussed. New interpretation of alkali metals' effect in the catalytic gasification process.